The role of Gelam honey in accelerating reepithelialization of ex vivo corneal abrasion model. Issue 4 (11th February 2021) - Azmi, Muhammad Fairuz; Abd Ghafar, Norzana; Che Hamzah, Jemaima; Chua, Kien Hui; Ng, Sook Luan
Abstract: This study aimed to investigate the role of Gelam honey (GH) in accelerating reepithelialization of corneal abrasion. Corneal epithelial cells (CEC) isolated from New Zealand white rabbit corneas, were cultured and circular‐shaped wounds were created onto them, representing the corneal abrasion model. These wounds were treated with basal (BM) and cornea media (CM) supplemented with GH. The percentage of wound closure was measured on day 0, 3, and 5. Expressions of cytokeratin 3 (CK3), cluster of differentiation 44 (CD 44), and connexin 43 (Cx43) were analyzed via qRT‐PCR and immunocytochemistry. The results showed CEC cultured in GH‐enriched media reepithelialized faster compared to control. Corneal abrasion treated with CM supplemented with GH closed completely on day 5. CK3, CD44, and Cx43 expressions correspond to the stages of reepithelialization. In conclusion, GH promotes the healing of the ex vivo corneal abrasion model. Further explorations of its potential as adjuvant therapy in treating corneal injuries are needed. Practical applications: Honey has been reported to have many medicinal properties including antibacterial, anti‐inflammatory, and the ability to promote skin wound healing. However, the effects of honey on corneal wound healing have not been fully elucidated. In the present study, we aimed to determine the effects of Gelam honey (GH), well‐known local honey obtained from the beehive of Gelam trees ( Melaleuca spp .), on the ex vivo corneal abrasion model via cell migration study and analysis of genes and proteins during corneal epithelial wound healing. GH has proven to have accelerated effects on the corneal epithelial cell migration during the closure of the ex vivo corneal abrasion wound model. The expressions of the genes and proteins of the corneal epithelial wound healing markers were in accordance with the stages of healing. Therefore, GH has the potential to be developed as adjuvant therapy in the form of GH‐based eye drop in treating corneal injuries. Abstract : Gelam honey (GH) accelerates the migration of corneal epithelial cells (CEC) during the reepithelialization process as demonstrated in this ex‐vivo corneal abrasion model. The expressions of the reepithelialization markers, namely CK‐3, the corneal epithelial cell differentiation marker, CD‐44, the adhesion proteins for cell‐to‐cell and cell‐to‐substrates interaction, and connexin‐43 (Cx43), the gap junction proteins, were increased during corneal reepithelialization. The highest expression of these markers, were seen in the group treated with corneal medium supplemented with GH, indicating the positive role of GH in the corneal abrasion healing process.